Comparison of acid, basic and enzymatic catalysis on the production of biodiesel after RSM optimization. (May 2019) - Tacias-Pascacio, Veymar G.; Torrestiana-Sánchez, Beatriz; Dal Magro, Lucas; Virgen-Ortíz, Jose J.; Suárez-Ruíz, Francisco J.; Rodrigues, Rafael C.; Fernandez-Lafuente, Roberto
Abstract: This paper shows the direct comparison of 4 different catalysts (homogenous alkaline (KOH), heterogeneous alkaline (CaO), homogenous acid (H2 SO4 ) and a new biocatalyst (lipase from Thermomyces lanuginosus (TLL) immobilized on octadecyl methacylate)) in the production of biodiesel from cooking oils. The reactions for each catalyst were optimized using response surface statistical methodology, considering as main parameters: substrates molar ratio, percentage of catalyst and reaction time, whereas for enzymatic catalysis instead reaction time, we studied water concentration. Alkaline homogenous catalysis was found to be the most effective, as expected from literature. However, for first time, the new biocatalyst from TLL is just around one order of magnitude under the homogenous catalysis in reaction rate and surpassed the heterogeneous catalysis or the acid catalysis (similar yields in 2 h versus the 1 h of the alkaline catalyst). Moreover, the reaction product using the biocatalytic approach was much cleaner and less energy demanding than the other catalytic approaches. From our view, this is the first report where biocatalysis is close to conventional catalysis in the production of biodiesel. Graphical abstract: Image 1 Highlights: Production of biodiesel using used cooking oil has been studied using alkaline, acid and enzymatic catalysis. Each strategy has been optimized by using response surface methodology approach. The good performance of the new TLL biocatalyst made it the second most efficient. Alkaline catalyst is the most effective, but the gap with biocatalysis is becoming smaller.